Психологічні особливості переживання працівниками ОВС стану самотності - Макаренко, П. В.; Makarenko, P. V. (Вісник Національного університету оборони України. - 2014. - Вип. 3(40). - С. 263-267, 2014)
Статтю присвячено дослідженню особливостей емоційних переживань працівників міліції з різним рівнем товариськості у стані самотності. Діагностовано, що працівники міліції усіх рівнів товариськості, перебуваючи у стані самотності схильні переживати негативні емоції: гнів, горе, відразу, почуття провини. Визначено, що стан самотності працівників міліції може виступати індикатором психологічного здоров’я особистості.

There are characteristics of emotional experiences of police officers with different levels of sociability in a state of loneliness shown in the article. For exploring of the characteristics of emotional experiences loneliness police officers with different levels of sociability was used the method of K. Izard’s differential emotions scale. There are snvestigated evaluated the intensity of the experience of emotion in the normal state and in a state of loneliness. The results showed that police officers at all levels of sociability, from low to high, while in a state of loneliness tend to experience negative emotions: anger, grief, guilt. Comparing the loneliness of physical pain that signals the presence of physical illness, loneliness can be a component of the regulatory system and act as an indicator of individual psychological health.

Статья посвящена исследованию особенностей эмоциональных переживаний работников милиции с разным уровнем общительности в состоянии одиночества. Диагностировано, что работники милиции всех уровней общительности, находясь в состоянии одиночества склонны переживать негативные эмоции: гнев, горе, сразу, чувство вины. Определено, что состояние одиночества работников милиции может выступать индикатором психологического здоровья личности.
Psychological features of experiencing psychic state of loneliness by police officers
Keywords: самотність; екстраверсія; інтроверсія; працівники ОВС; емоційні переживання; психологічні особливості; loneliness; extroversion; introversion; police officers; emotional experiences; psychological features; одиночество; экстраверсия; интроверсия; работники ОВД; эмоциональные переживания; психологические особенности